Bacteriophage Interference in Bacillus subtilis 168 - Yasbin, R. E. (1974)
Strains of Bacillus subtilis lysogenic for temperate bacteriophage SPO2 inhibit the development of bacteriophage φ1. After infection by bacteriophage φ1, DNA and RNA synthesis in the lysogenic host terminates, culminating in cell death. Bacteriophage SPO2 also prevents the production of bacteriophage φ105. Mechanisms for these two types of bacteriophage interference are discussed.